The Disaster Management Operational Service - Tóth, Tibor; Tímár, Tamás (Magyar Rendészet, 2016)
The national disaster management system in Hungary has improved significantly in the past several years. The Disaster Management Act of 2011 fundamentally changed the structure of the emergency management system and complementary regulations now include mandatory functions. One of the elements of this renewed structure is the Disaster Management Operational Service (DMOS), which entered operational phase as a separate organisational body in every Hungarian county as well as the capital on April 1, 2012. The county directorates are obliged to run a standby service to have professionals on duty at all times in 24/48 shifts. DMOS actions can be intervention in fire emergencies, technical rescue, exercises, control activities and the fire investigation.